FEATURES OF THE USE OF MODERN TECHNOLOGIES IN MEDICAL PEDAGOGICAL PRACTICE USING THE EXAMPLE OF ENDOCRINOLOGY - Kdirbaeva , F (Uzbekistan Open Conference, 2025)
Adult education in our country is undoubtedly becoming an increasingly important area of educational services, it plays a leading role in the implementation of the concept of lifelong education. The final work outlines the main provisions and principles of andragogy, discusses the problems and prospects for its development. And also, the methodology for the rational application of new pedagogical methods «CAUSE AND EFFECT» in conducting practical classes is highlighted.
Keywords: endocrinology; trainees; pedagogical technology; andragogy